O My Friends, There is No Friend - Hern, Matt; Johal, Am (transcript Verlag, 2024)
Can friendship as a political practice offer enough traction to imagine a borderless world? The startling contemporary rise in aggressive ethno-nationalism and end-times ecological crises have the same root: an inability to be together with humans as much as the natural world. Matt Hern and Am Johal suggest that porous renditions of being-together animated by friendship can spark a repoliticization of the political to surpass the foreclosures of the state, speak to a freedom of movement, and find renovated relationships with the more-than-human. This volume includes interviews with Jean-Luc Nancy, Leela Gandhi and Leanne Simpson.